Where Did the Pericardial Effusion Go? A Case of Cardiopulmonary Resuscitation Acting as Treatment for Pericardial Tamponade - Varun tej Gonuguntla; Parita Soni; Nishil Dalsania; Ravi Karan Patti; Somal Navjot; Seneviratne Chanaka; Yizhak Kupfer (Case Reports in Critical Care)
Pericardial tamponade results in multiple organ dysfunction and can lead to cardiac arrest. Cardiopulmonary resuscitation (CPR), a life-saving measure performed on patients in cardiac arrest, can lead to thoracic organ damage. However, CPR rarely acts as a therapeutic treatment for pericardial tamponade. Our case describes a patient admitted with pericardial tamponade in whom CPR provided therapeutic treatment with pericardial rupture and resolution of the tamponade.